Determination of composite friction factor and manning roughness coefficient for Discharge estimation in natural compound channels - Lai, Sai Hin (Universiti Malaysia Sarawak, UNIMAS, 2005)
A field study has been carried out at University Malaysia Sarawak (UNIMAS), aimed at a fuller understanding of the mechanics flow and also at evolving more accurate methods for overbank flow discharge estimation. The study involved four frequently flooded rivers with extensive data collected.